Substrate properties modulate cell membrane roughness by way of actin filaments - Chao-Hung Chang (Nature Portfolio, 2017)
Abstract Cell membrane roughness has been proposed as a sensitive feature to reflect cellular physiological conditions. In order to know whether membrane roughness is associated with the substrate properties, we employed the non-interferometric wide-field optical profilometry (NIWOP) technique to measure the membrane roughness of living mouse embryonic fibroblasts with different conditions of the culture substrate. By controlling the surface density of fibronectin (FN) coated on the substrate, we found that cells exhibited higher membrane roughness as the FN density increased in company with larger focal adhesion (FA) sizes. The examination of membrane roughness was also confirmed with atomic force microscopy. Using reagents altering actin or microtubule cytoskeletons, we provided evidence that the dynamics of actin filaments rather than that of microtubules plays a crucial role for the regulation of membrane roughness. By changing the substrate rigidity, we further demonstrated that the cells seeded on compliant gels exhibited significantly lower membrane roughness and smaller FAs than the cells on rigid substrate. Taken together, our data suggest that the magnitude of membrane roughness is modulated by way of actin dynamics in cells responding to substrate properties.